Keanekaragaman Tumbuhan Toga dan Pembudidayaannya melalui Taman Konservasi Toga di Desa Timbuseng - Muhammad Ammar Naufal; Nurfadillah; Zaky An Nabil; Mardin; Uun Ade Arjun (Jurusan Matematika FMIPA UNM, 2023)
The Student Organization Capacity Strengthening Program (PPK Ormawa) is one of the activities under the auspices of the Ministry of Education and Culture which is participated in by universities throughout Indonesia. PPK Ormawa aims to improve the quality of Ormawa and at the same time develop students' soft skills and competencies such as organizational abilities, strengthening the character of Pancasila, defending the country, love of the homeland and nationality, leadership, and working together (team work). Students implementing PPK Ormawa are expected to be able to utilize this activity to hone their skills in critical, creative thinking, problem solving, communicative, collaborative, information technology literate, have a leadership spirit, act positively and productively based on the urge of their conscience, have a sense of caring and contribute to the community in the village/subdistricts so that active, independent, entrepreneurial and prosperous target areas are built.